Association of CCL4 rs10491121 and rs1634507 gene polymorphisms with cancer susceptibility: trial sequential analysis and meta-analysis - Yang, Changsen; Song, Tiangang; Mo, Yajie; Wu, Peixuan; Tian, Haokun; Wen, Lequan; Gao, Yun (Frontiers in Oncology, 2023)
Background: Although numerous case-control studies have explored the association between CC cytokine ligand-4 (CCL4) expression and cancer susceptibility, their results have been conflicting. This study aimed to determine the still-unknown connection of CCL4 rs10491121 and rs163450 polymorphisms with cancer susceptibility. Methods: Several databases, such as Web of Science, PubMed, and EMBASE, were searched for papers published since the creation of the database until November 2, 2022. Using RevMan 5.4 and StataMP 17 softwares, meta-analysis and subgroup analysis were performed after article screening and data extraction. For sensitivity analyses, one-by-one exclusion method was used, and then, the comprehensive effect was estimated and compared with that before exclusion. Trial sequential analysis (TSA)was performed using TSA 0.9.5.10 beta software. Results: Seven case-control studies encompassing 3559 cases and 4231 controls were included. The P value was greater than 0.05 for all models, indicating the absence of an evident relationship of CCL4 gene rs10491121 and rs1634507 polymorphisms with cancer susceptibility. However, in the subgroup analysis of rs10491121, the P values in all models studied by us except GA vs. AA were <0.05 considering the Chinese subgroup, suggesting that the G allele is a risk factor for cancer in the Chinese population. Besides, in the subgroup analysis of rs1634507 considering oral cancer, the co-dominant model GG vs. TT, dominant model GG + GT vs. TT, and allele model G vs. T groups showed OR < 1 and P < 0.05, indicating that the G allele was a protective factor of oral cancer. However, for other cancer types, all the models studied by us except GG vs. GT showed OR > 1 and P < 0.05, indicating that the G allele was a risk factor for these other cancers. Despite the statistically significant results, sensitivity analysis had some stability limitations, and TSA results suggested the possibility of false positives. Conclusion: For rs10491121, we identified an association between the G allele and increased cancer risk in the Chinese population. For rs1634507, the G allele was not found to be associated with reduced risk of oral cancer and increased risk of other cancers studied by us.